A case of "chronic mountain sickness" in the United States - Hetch, Hans H. (1958)
1.-A case of Chronic Mountain Sickness is described at a resident of the Rocky Mountains of Colorado. There have been clinical, electrocardiographic and cardiopulmonary physiology studies. Symptoms, signs and electrocardiographic abnormalities disappeared when the patient down to sea level. However, it has been possible to bring out a intensely lightweight persistent lung disease after residence at sea level for more than two years. 2. can be assumed that some cases of chronic mountain sickness are the result of disturbances in the respiratory gas exchange abnormalities and ventilation perfusion indices based on a very slight intrinsic lung disease, to cause signs or symptoms at the level of sea.